The impact of psychosocial safety climate on the intervention effect of psychotherapeutic consultation at work in Germany - secondary analysis of a randomized controlled trial - Heming, Meike; Hander, Nicole; Gündel, Harald; Feißt, Manuel; Hansmann, Marieke; Kröger, Christoph; Mulfinger, Nadine; Weber, Jeannette; Herold, Regina; Schröder, Ute; Wegewitz, Uta; Angerer, Peter (BMC public health, 2025)
Background: Psychotherapeutic consultation at work (PT-A) aims to reach employees at risk of or suffering from common mental disorders early by offering low-threshold consultation that combines person-related and work-related modules. In addition to this individual-level approach, it is suggested that the psychosocial safety climate (PSC) in an organization precedes psychosocial working conditions and impacts employees' psychological health. The PSC reflects employees' perceptions regarding the extent to which psychological health and safety are prioritized by the management. However, little is known about the role of PSC on the intervention effect in participants receiving PT-A. Therefore, this study aims to investigate whether PSC moderates the effect of PT-A on self-reported depressive symptoms, anxiety, and general health status. Methods: As a secondary analysis, this study analyzed data on participants (n = 549) from a multicenter randomized controlled trial in Germany evaluating the effectiveness of PT-A. Participants completed a baseline questionnaire (T0) and follow-up questionnaires nine months (T1) and 15 months later (T2). They provided information on general health status (one item of the 12-items Veterans RAND health survey), depressive symptoms (Patient-Health-Questionnaire-9), anxiety symptoms (Generalized Anxiety Disorder Scale-2) and the four-item PSC questionnaire. To investigate the role of PSC for the intervention effect, an interaction term (PSC*treatment group) was included in multiple linear regression analyses estimating (mental) health indicators at either T1 (n = 411) or T2 (n = 362). Analyses were adjusted for sex, age and occupational level. Results: Participants in the intervention group reported a significant symptom reduction nine and 15 months after PT-A. In terms of direct effects, PSC was negatively associated with anxiety symptoms at T1 (B = 0.16, p = .04). PSC did not moderate the intervention effect on depressive symptoms, anxiety symptoms or general health status. Conclusions: Findings indicated a significant symptom reduction after PT-A, and showed that PSC does not play a role in the extent of symptom reduction among employees in Germany. However, PSC may need to be improved in German workplaces and its effect on individual-level symptoms regarding common mental disorders (CMD) should be further investigated. Trial registration: The RCT was registered at the German Clinical Trial Register on 01.03.2021 (DRKS00023049) https//drks.de/search/en/trial/DRKS00023049.
Veröffentlicht: 22. Oktober 2025
Gesehen am 09.12.2025